Towards understanding of fungal biocontrol mechanisms of different yeasts antagonistic to Botrytis cinerea through exometabolomic analysis - Millan, Alicia Fernandez-San; Gamir, Jordi; Larraya, Luis; Farran, Inmaculada; Veramendi, Jon (Biological control, 2022)
[Display omitted] •The yeast exometabolome changes after co-culture with a fungal pathogen.•Both general and yeast strain-specific metabolites are differentially secreted.•Several metabolites have antifungal properties in vitro but only two in vivo.•Trans-cinnamic acid is the best antifungal metabolite secreted by yeasts.•Indole-3-carboxaldehyde shows lower levels of protection. There is increased interest in research on yeasts as potential phytopathogen biocontrol agents due to increasing restrictions in the use of chemical pesticides. Yeast strains from a range of genera and species have been reported to inhibit postharvest decay in different fruits. However, the mechanisms behind these yeast biocontrol capacities have not been completely deciphered because they are complex and act synergistically. In this study, we performed a thorough untargeted analysis of the exometabolome generated in a co-culture of the fungal plant pathogen Botrytis cinerea with four antagonistic yeast strains: Pichia fermentans (two strains), Issatchenkia terricola and Wickerhamomyces anomalus. As a result, general and strain-specific antifungal mechanisms and molecules were identified. The P. fermentans strains secreted the highest number of differential metabolites to the extracellular medium when co-cultured with B. cinerea. In vitro antagonistic and in vivo pathogen protection assays were performed with the selected metabolites. Among a plethora of 46 differentially secreted metabolites related to yeast-fungus competitive interaction, the phenylpropanoid trans-cinnamic acid and the alkaloid indole-3-carboxaldehyde were identified as the best antagonistic metabolites against gray mold infection under in vivo protection assays. Both metabolites caused damage to the fungal membrane and increased ROS generation in spores of B. cinerea. In addition, enhanced yeast secretion to the extracellular medium of oxylipins, dipeptides, alkaloids or antibiotics deserve to be further investigated as signaling or antagonistic molecules. This study opens the door to future investigations of roles of these molecules in yeast metabolism and application of this knowledge for biotechnological purposes.